3D Programming for windows : three-dimensional graphics programming for the windows presentation foundation - Petzold, Charles (United States of America: Microsoft Press, 2008)
Get a focused introduction to programming 3D graphics with the Windows Presentation Foundation 3D API. Complementing his book Applications = Code + Markup, award-winning author Charles Petzold builds on XAML essentials, teaching you how to display and animate 3D graphics under the Microsoft .NET Framework 3.0 and Windows Vista. You’ll get expert guidance and code samples in XAML and Microsoft Visual C#©— helping you master the skills you need to create high-fidelity user interfaces
Resumen tomado de la web
Audiencia general
Keywords: Windows (programas para computador)